La violencia intrafamiliar y su influencia en el desarrollo de la autoestima de los niños y niñas de primer año de educación básica de la escuela fiscal Lic. Diego Minuche Garrido en la ciudad de Machala, periodo lectivo 2011 - 2012. - Quito Vázquez, Luz Angélica (2015)
Well as violence in the family is known, is a problem that has affected the families of all societies always, this results mainly psychological and physical harm. This research was conducted in fiscal School "Lic Minuche Diego Garrido." Belonging to the city of Machala El Oro province, the central problem: how domestic violence affects the self-esteem of children freshmen Basic school education tax Lic Minuche Diego Garrido. city of Machala, academic year 2011 - 2012 ?, which raises aimed to determine the causes that cause domestic violence and impair self-esteem in homes children. For the execution of this research work inductive-deductive, hypothetical-deductive theory and statistical methods they were used. Regarding the use of techniques of direct observation technique, interview was used, and survey which was of great help to the verification of the hypotheses. The lack of communication, the few expressions of affection, not to forgive, pride, are some of the main factors that flow to that family violence is a bad constant in all families.